Gain in net survival from hypertension control over the last half-century. (16th July 2021) - Lantelme, Pierre; Moulayat, Chahinaz; Courand, Pierre-Yves; Mouly-Bertin, Carine; Debouzy-Berge, Constance; Rial, Marie-Odile; Iwaz, Jean; Harbaoui, Brahim; Riche, Benjamin; Rabilloud, Muriel
Abstract: Aims: This study determined whether the improvements in hypertension management over the last five decades have influenced subjects' prognosis. Methods and results : The study considered 5693 eligible subjects seen January 1969 to February 1991 (follow-up until December 2003) or January 1995 to October 2014 (follow-up until July 2016) in an all-grade hypertension reference centre. Missing data or incomplete follow-ups led to exclude 1036 subjects (18%). The outcome was all-cause death. An adjusted modelling of the excess mortality rate assessed subjects' net survival over five inclusion periods to allow for the increase in life expectancy of the general population during the same periods. The analysis of 4657 records (mean age: 47 years; 43.2% women) showed that the proportion of subjects with grade 3 hypertension decreased significantly from 43.3% (1142) to only 6.3% (22) over the five periods and that the net survival improved in men and women regardless of the hypertension grade; i.e. the gain in net survival at 15 years was estimated at 12.3% (95% confidence interval: 8.1–22.3). The 15-year restricted mean survival was estimated at 13 years over the first period and 14.8 years over the last period, which is nearly a 2-year gain in life expectancy at 15 years. Conclusion : Since the 70s and the advent of modern management, the excess mortality of hypertensive subjects (vs. the general population) was markedly reduced. Within a context of trivialization of blood pressure measurement and reluctance to long-term treatments, physicians should consider this advantage and use it to promote blood pressure control.